2014
DOI: 10.1128/jcm.03593-13
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Invasive Candida glabrata in Patients on Micafungin: a Novel FKS Gene Conversion Correlated with Sequential Elevation of MIC

Abstract: c Candida glabrata strains sequentially isolated from blood developed resistance to micafungin (MICs from <0.015 to 4 g/ml). A novel mutation identified in micafungin-resistant strains at bp 262 of FKS2 (containing a deletion of F659 [F659del]) was inserted into the homologous region in FKS1. CASE REPORTA 93-year-old man was admitted to our hospital with a diagnosis of pulmonary tuberculosis (day 1). The patient had been receiving treatment for essential hypertension with chronic renal failure for a decade. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…In general, in current treatment guidelines, a lower dose of micafungin (50 mg/day) has been approved for use for prophylactic administration (11,12). This is probably why there are only a few studies on the development of BC when a sufficient dose of micafungin (Ն100 mg/day) is provided (9,17). Among the 13 strains that caused BC during micafungin treatment and for which a breakpoint was established and antifungal susceptibility testing was performed, 11 strains were susceptible to micafungin in vitro (85%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, in current treatment guidelines, a lower dose of micafungin (50 mg/day) has been approved for use for prophylactic administration (11,12). This is probably why there are only a few studies on the development of BC when a sufficient dose of micafungin (Ն100 mg/day) is provided (9,17). Among the 13 strains that caused BC during micafungin treatment and for which a breakpoint was established and antifungal susceptibility testing was performed, 11 strains were susceptible to micafungin in vitro (85%).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of BC among all patients with hematological malignancies and candidemia was previously found to range from 19% to 72% (3)(4)(5). According to the findings of some previous studies focused on BC, risk factors for BC are severe neutropenia, the use of corticosteroids, the presence of a central venous catheter (CVC), and resistance to antifungal agents (6)(7)(8)(9)(10). Furthermore, a recent multicenter study found that the causes of BC, particularly in patients with BC receiving azole or liposomal amphotericin B, might be associated with microbiological factors, such as resistance to antifungal agents, and/or host factors, such as neutropenia or the presence of a CVC (7).…”
mentioning
confidence: 99%
“…However, resistance to echinocandins in Candida spp. has also appeared in recent years with the highest rate occurring among C. glabrata and breakthrough invasive C. glabrata infections have been reported in patients on micafungin therapy [14][15][16][21][22][23][24] . Resistance to polyenes is also being reported with increasing frequency in clinical C. glabrata isolates [25][26][27][28][29] and a multidrug-resistant phenotype (resistant to azoles and echinocandins) occurring in ICU and non-ICU settings has also been described in recent years 30,31 .…”
mentioning
confidence: 99%
“…Acquired resistance to echinocandins has been reported in C. albicans, with some isolates containing the same S645P mutation in HS-1 of the FKS1 gene (30,32,33). Echinocandin resistance is particularly alarming in C. glabrata because nearly one-third of clinical isolates of this haploid species are also intrinsically resistant to azoles (38)(39)(40). Mutations in HS-1 and HS-2 of both FKS1 and FKS2 genes confer resistance to echinocandins in C. glabrata (12,13,40).…”
mentioning
confidence: 99%